The Rise of Public and Private Digital Money : A Strategy to Continue Delivering on The IMF's Mandate. (Policy Papers; Policy Paper ;, 2021)
Following the companion paper on the new policy challenges related to the adoption of digital forms of money, this paper presents an operational strategy for the IMF to continue delivering on its mandate of ensuring domestic and international financial and economic stability. The paper begins by summarizing the forces driving the adoption of digital forms of money, and the new policy questions that emerge. It then focusses on how the IMF's core activities and output will need to evolve, including surveillance, capacity development, and analytical foundations. It ends by discusses how the IMF intends to partner with other organization, and to grow and structure internal resources to fulfill this vision.